AN EMPIRICAL DETERMINANT OF EQUITY SHARE PRICE OF SOME QUOTED COMPANIES ON THE NIGERIAN STOCK EXCHANGE - Adebayo, OLOIDI, Gabriel; S. K, BOLADE, (IJRDO - Journal of Business Management, 2015)
The study analyzed the major variables that determine the equity share price of listed companies on the Nigerian Stock Exchange [NSE] publication as at 2011/2012 edition. Eighty companies were examined. The quoted price of the shares on 4th January 2011 was estimated by other explanatoryvariables.OLS regression was used to analyse cross-sectional [non– time series] data. Findings revealed that the previous year share price significantly and positively influenced equity share price at α=0.000 and earnings per share was negatively significant at α=0.05. The last was dividend per share, positively and significantly influenced equity share price at α=0.014. The combined three variables explained the variation in equity share at an adjusted R – square value of 0.969. This showed that about 97 percent of the determinants of equity share price had been explained by these three explanatory variables.